2006
DOI: 10.1115/1.2427081
|View full text |Cite
|
Sign up to set email alerts
|

Response of Backflow to Flow Rate Fluctuations

Abstract: The response of backflow at the inlet of an inducer to the flow rate fluctuation is studied by using three-dimensional numerical calculations based on the k-ϵ turbulence model for the discussion of its effect on cavitation instabilities. It is first shown that the size of the backflow region can be correlated with the angular momentum in the upstream and the phase of the backflow significantly delays behind the quasi-steady response even at a very low frequency. It is then shown that the conservation relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[8] Response of backflow to flow rate fluctuation was discussed from the balance of angular momentum at the inlet. [9] The angular momentum transfer by the backflow was in anti-phase with the flow rate fluctuation. [10] The angular momentum transfer by the normal flow was larger when the angular momentum in the upstream is larger.…”
Section: Methods Of Analysis and Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Response of backflow to flow rate fluctuation was discussed from the balance of angular momentum at the inlet. [9] The angular momentum transfer by the backflow was in anti-phase with the flow rate fluctuation. [10] The angular momentum transfer by the normal flow was larger when the angular momentum in the upstream is larger.…”
Section: Methods Of Analysis and Geometrymentioning
confidence: 99%
“…Calculations were made by using a commercial code CFXTASCflow based on RANS with the k-ε turbulence model [9]. For the simulation of the backflow vortex structure, it is required to use a LES code [10] and the present calculation could not simulate the vortex structure.…”
Section: Methods Of Analysis and Geometrymentioning
confidence: 99%
“…A lot of work has been performed to describe both experimentally and numerically its dynamics (see e.g., Refs. [18][19][20][21][22][23]. The backflow consists in a rotating annular free shear layer in which the diphasic content of the eddies may vary with respect to the inducer inlet cavitation number.…”
Section: A Backgroundmentioning
confidence: 99%
“…Backflow from the inducer has a swirl velocity of about 20-30% of tip velocity and a backflow vortex structure is formed at the shear layer between swirling backflow and straight main flow. Experimental and computational studies of the backflow and backflow vortex of inducer have been reported [1][2][3].…”
Section: Introductionmentioning
confidence: 99%